From short exact sequences of abelian categories to short exact sequences of homotopy categories and derived categories - Yilin Wu; Guodong Zhou (Electronic Research Archive, 2022)
We show that a short exact sequence of abelian categories gives rise to short exact sequences of abelian categories of complexes, homotopy categories and unbounded derived categories, refining a result of J. Miyachi.